Governing Jevons' Paradox: Policies and systemic alternatives to avoid the rebound effect - Jaume Freire-González (Energy Research & Social Science, 2021)
In this article we lay the foundations for a new approach for Jevons Paradox and rebound effects, based on how it is triggered (origin) and how it expands (expansion), and from it, explore the potential of different ways to minimize or offset rebounds from resources productivity and conservation. We conceptualize different key aspects to understand and reframe rebound effects. On the “origin” side, we introduce the key concept of “resource-efficient paths”, to show how productivity is a changing and complex issue, affected by the interaction of all other resources that produce goods or services, as well as behavior. This is a necessary, but not sufficient condition for the existence of rebound effects. On the “expansion” side we introduce the notion of systemic insatiability as key in the expansion and consolidation of rebounds through socioeconomic systems, and sufficient condition for the existence of rebound effects. Moreover, we analyze how inequality can exacerbate insatiability. With this framework in mind, we examine two main positions to find solutions: In the first, under our current socioeconomic, cultural, and institutional structures, we analyze different means of public policy intervention: resources pricing, cap-and-trade systems, regulation, and voluntary actions. The second position implies tackling systemic changes. Here we explore different post-growth systemic alternatives: steady-state, degrowth, agrowth, and post-development intellectual currents in relation to rebounds and Jevons Paradox.
Keywords: 330